In Vivo 3T Magnetic Resonance Imaging Using a Biologically Specific Contrast Agent for Prostate Cancer: A Nude Mouse Model. (31st May 2017) - Abraham, Christopher Brian; Jani, Prashant; Turuba, Roxanne; Campbell, Michael; Zehbe, Ingeborg; Curiel, Laura
Abstract : We characterized in vivo a functional superparamagnetic iron-oxide magnetic resonance contrast agent that shortens the T 2 relaxation time in magnetic resonance imaging (MRI) of prostate cancer xenografts. The agent was developed by conjugating Molday ION™ carboxyl-6 (MIC6), with a deimmunized mouse monoclonal antibody (muJ591) targeting prostate-specific membrane antigen (PSMA). This functional contrast agent could be used as a noninvasive method to detect prostate cancer cells that are PSMA positive and more readily differentiate them from surrounding tissues for treatment. The functional contrast agent was injected intravenously into mice and its effect was compared to both MIC6 (without conjugated antibody) and phosphate-buffered saline (PBS) injection controls. MR imaging was performed on a clinical 3T MRI scanner using a multiecho spin echo (MESE) sequence to obtain T 2 relaxation time values. Inductively coupled plasma atomic emission spectroscopy was used to confirm an increase in elemental iron in injected mice tumours relative to controls. Histological examination of H&E stained tissues showed normal morphology of the tissues collected.